Morbiditas dan Mortalitas Dini Pasca-Sistektomi Radikal pada Kanker Buli-Buli di RSCM, 1999 - 2009 - MASFAR, ILHAM WAHYUDI; MOCHTAR, CHAIDIR ARIEF; UMBAS, RAINY (Indonesian Journal of Cancer, 2010)
Purpose: to evaluate early morbidity and mortality rateÂ  after radical cystectomy and urinary diversion also the prognostic factor(s). Material and method: we retrospectively collected data from medical records patient who underwent radical cystectomy and urinary diversion at RS. Cipto Mangunkusumo during 1999 â 2009 period.Descriptive evaluation was done on number and type of morbidity and mortality. Modified Clavien System was used as standarized complication report method. Prognostic factors were analyzed.Result: there was 62.9% of early morbidity rate, 11% of early mortality rate, 40% of major morbidity according modified Clavien System. None of prognostic factors were statistically significant.Conclusion: early morbidity rate was similar to other reports. But rate of early major morbidity and mortality were higher. This is probably due to higher number of preoperative comorbidities, more advanced tumor stage, and low hospital volume for this particular procedure compared to others.